2003
DOI: 10.1021/ma034291i
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition from Disordered Sphere to Hex-Cylinder via Transient Ordering into Bcc-Sphere in SIS Triblock Copolymer

Abstract: We have investigated the ordering processes from the disordered-sphere phase (designated hereafter disordered sphere), where spherical microdomains exist but they have only a short-range liquidlike order, to the phase of hexagonally packed cylindrical microdomains (designated hereafter hex-cylinder), induced by the temperature drop (T-drop). The block copolymer studied is a compositionally asymmetric polystyrene-block-polyisoprene-block-polystyrene triblock copolymer and forms disordered sphere above the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 74 publications
13
57
0
Order By: Relevance
“…These profiles are not deliberately corrected for slit smearing to prevent any artifacts. As in the previous studies, [30,31] the freeze-in process in this study hardly changes the characteristics of the profiles at small q region (q! 0.4 nm K1 ).…”
Section: Saxs Profiles Measured Before and After Freezingsupporting
confidence: 82%
See 3 more Smart Citations
“…These profiles are not deliberately corrected for slit smearing to prevent any artifacts. As in the previous studies, [30,31] the freeze-in process in this study hardly changes the characteristics of the profiles at small q region (q! 0.4 nm K1 ).…”
Section: Saxs Profiles Measured Before and After Freezingsupporting
confidence: 82%
“…Moreover, a broad scattering maximum at qZ 0.57 nm K1 marked by a thick arrow can be seen in the profile after freezing but not in that before freezing. This maximum indicates that the particle scattering from spheres, namely the scattering from form factor, appears because the interface between PS spheres and PI matrix is sharpened by freezing, as reported in the previous studies [30,31]. Point (2) in Fig.…”
Section: Saxs Profiles Measured Before and After Freezingsupporting
confidence: 70%
See 2 more Smart Citations
“…Some authors have suggested distinguishing this ODT from that observed for gyroid, cylinder, or lamellar samples, by terming it the lattice disordering transition. [27][28][29][30] If there are distinct micelles present above the ODT, then at sufficiently high-temperature such micelles should disperse in favor of free chains. Evidence for a "critical micelle temperature" (cmt) has been presented in bulk diblocks, although it should be recognized that such a cmt does not represent a true thermodynamic phase transition.…”
Section: Introductionmentioning
confidence: 99%